EFFECT OF ALOIN EXTRACT ON THE INCREASE OF FIBROBLAS CELL EXPRESSION ON HEALING OF WOUND WOUNDS OF HORSE WHITE RATS (Rattus norvegicus) BY THE AGING PROCESS - Dewi , Nadia Purnama; Vedora, Monica Putri; Vani, Ade Teti; Abdullah, Dessy; Triansyah, Irwan (MSJ : Majority Science Journal, 2023)
Motivation/Background: The wound healing of aging skin can be assisted by using aloin that increases fibroblast cells. The aim of this research is to determine the effect of aloin extract on increasing fibroblast cells in wound healing in male rats (Rattus norvegicus) with aging process The method research is a post-test control group design. The research sample use twenty-four of six months male rats (Rattus norvergicus) which were divided into 4 groups. Fibroblast assessment was carried out on days 7 and 14 of aloin treatment. Fibroblast data was processed using normality test and significance tests, carried out using the measured repeated test followed by Bonferonni test. The results is highest number of fibroblasts on day 7 was in the control group (+) treated with 10% povidone iodine. The highest number of fibroblasts on day 14 was in treatment group 2 which was given aloin. The statistical test Measure Repeated test said that there was no significant difference between the control and treatment groups p = 0.503 (p> 0.05). However, in the Bonferonni post hoc test, the value of p = 0.000 was obtained, which means that giving aloin can increase the number of fibroblast cells. The conclusions is aloin extract increased the number of fibroblast cells in wound healing of male rats (Rattus norvegicus) with aging process, which has the same effectiveness as povidone iodine